ANALYSIS OF THE SUFFICIENCY OF PADDY PRODUCTION TO FULFILL THE NEEDS OF THE POPULATION IN PADANG CITY YEAR 2020 TO 2025 - Paus Iskarni (JURNAL GEOGRAFI, 2022)
This study aims to see; changes in the use of agricultural land (rice fields), population growth, the carrying capacity of lowland rice agricultural land to meet the food needs of the population, and projecting food needs (rice) for the residents of Padang City from 2020 to 2025 as well as analyzing the level of food sufficiency (rice) based on land change patterns agriculture, then see how the growth rate of food production and population growth rate in the city of Padang. The research method used in this research is descriptive quantitative. Spatial data is processed by Geographic Information Systems (GIS), and demographic formulas process population data. The land's carrying capacity is obtained from the comparison between available land, production, and population. The results of this study indicate the shrinkage of the agricultural land area of 100.86 ha/year. The most extensive agricultural land depreciation range occurred from 2010 to 2011. The population growth ratio of Padang City between 2000-2010 was successfully reduced to 1.57 per year, with a population increase of 112,779 people or 15.64%. The population growth of Padang City is in the range of 1.57 and is not supported by the growth of lowland rice production. In 2025, the city of Padang is still classified as a class III region (σ < 1) or an area that has not been able to meet its own food needs (self-sufficiency). Land shrinkage and a decrease in harvested area and productivity have caused the carrying capacity of paddy fields in Padang City to continue to decline.Keywords: Sufficiency, Rice Production, Population Needs